John Lilly, The Mind of the Dolphin, and Communication Out of Bounds - Bruce Clarke (communication +1, 2014)
In this essay I develop a systems-theoretical observation of John Lilly’s cybernetics of communication in his 1967 work The Mind of the Dolphin. The eight-year-old project that The Mind of the Dolphin recounts for public consumption details his aspiration to achieve an unprecedented breakthrough beyond companionate communion to fully abstract linguistic communication across species boundaries. Between 1959 and 1968 Lilly wagered and lost his mainstream scientific career largely over this audacious, ultimately inconclusive bid to establish and document for scientific validation “communication with a nonhuman mind.” In that effort, however, he mobilized the best available tools, a cutting-edge array of cybernetic concepts. He leaned heavily on the information theory bound up with first-order cybernetics and operated with heuristic computational metaphors alongside the actual computers of his era. As I will elicit through some close readings of his texts, in that process Lilly also homed in on crucial epistemological renovations with a constructivist redescription of cognition that may have influenced and motivated his colleague Heinz von Foerster’s more renowned formulations, arriving in the early 1970s, of a second-order cybernetics.